PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Kumangki, Nadiah Fadhilah; Cahyonowati, Nur (Diponegoro Journal of Accounting, 2021)
This study aims to determine whether the intellectual capital has a positive effect on profitability. This study is a replication of the research that has been done by Firer and Mitchell Williams (2003). Replication is done by using intellectual capital which is proxied by VAIC as independent variable, profitability as dependent variable which measured by return on asset, and control variable consisting of firm size. This study uses secondary data from the annual financial statements of banks which listed in Indonesian Stock Exchange for 2017-2019 period. Data were collected by using documentation method and samples were determined by using purposive sampling. Samples used in this study were 26 banking companies. This research uses panel data regression analysis with Eviews 9 analysis tool. The result showed that intellectual capital has a positive and significant effect on the profitability of the banking companies which listed in Indonesian Stock Exchange from 2017 to 2019.